Role of chitosan in titanium coatings. trends and new generations of coatings - López-Valverde, Nansi; Aragoneses, Javier; López-Valverde, Antonio; Rodríguez, Cinthia; Macedo de Sousa, Bruno; Aragoneses, Juan Manuel (Frontiers in Bioengineering and Biotechnology, 2022)
Survival studies of dental implants currently reach high figures. However, considering that the recipients are middle-aged individuals with associated pathologies, research is focused on achieving bioactive surfaces that ensure osseointegration. Chitosan is a biocompatible, degradable polysaccharide with antimicrobial and anti-inflammatory properties, capable of inducing in-creased growth and fixation of osteoblasts around chitosan-coated titanium. Certain chemical modifications to its structure have been shown to enhance its antibacterial activity and osteoinductive properties and it is generally believed that chitosan-coated dental implants may have enhanced osseointegration capabilities and are likely to become a commercial option in the future. Our review provided an overview of the current concepts and theories of osseointegration and current titanium dental implant surfaces and coatings, with a special focus on the in vivo investigation of chitosan-coated implants and a current perspective on the future of titanium dental implant coatings.